Prevalence of inappropriateness of elemene injection for hospitalized cancer patients: a multicenter retrospective study - Cen, Mingzheng; Jiang, Guojun; Zhao, Yuhua; Yu, Zhenwei; Li, Minxian (Frontiers in Pharmacology, 2024)
Background: Elemene injection could provide clinical benefit for the treatment of various cancers, but the clinical evidence is weak. Thus, its wide use in China has raised concerns about the appropriateness of its use. Methods: This was a multicenter retrospective study to evaluate the prevalence of inappropriateness of elemene injection for hospitalized cancer patients. Patients who met the inclusion criteria were retrospectively included, and demographic characteristics were extracted from the hospital information systems. The inappropriateness of elemene injection use was assessed using the preset criteria, and the prevalence was calculated. Multivariate logistic analysis was applied to identify any factors associated with inappropriate use. Results: A total of 275 patients were included in the analysis. The median age was 62 years, and 30.9% were females. The most common cancer was lung cancer (24.0%), and 68.2% of the patients were receiving chemotherapy. The overall prevalence of inappropriateness was 61.8%. The most common reason for inappropriateness was inappropriate indications, and the second was inappropriate doses. Age and oncological department were significant risk factors associated with inappropriate use, while lung cancer, liver cancer and admission to cardiothoracic surgery were associated with a low risk of inappropriate use. Conclusions: The prevalence of inappropriateness among hospitalized elemene injection users was high. More efforts, especially those to improve the appropriateness of indications, should be made to improve the rational use of elemene, as well as other complementary medicines. Physicians should take caution to avoid inappropriate use when prescribing drugs with limited clinical evidence.